Degradation and utilization by Butyrivibrio fibrisolvens H17c of xylans with different chemical and physical properties. - Hespell, R B (1995)
Hemicelluloses, mainly xylans, can be a major component of diets consumed by ruminants and undergo various degrees of microbial digestion in the rumen. The ability of Butyrivibrio fibrisolvens, a major xylanolytic ruminal species, to degrade and utilize nine chemically and physically different xylans for growth was examined. The arabinoxylans used included two isolated from corncobs (CCX-A and CCX-B), a native xylan excreted by corn cell tissue cultures (CX), an oxalic acid-treated, arabinose-depleted CX, and oat spelt xylan. Except for CCX-A, these xylans were extensively converted within 3 h of growth to acid-alcohol-soluble forms that remained at high levels for the duration of culture growth. These xylans contain mainly xylose and arabinose with small amounts of uronic acids. For a given xylan, all three components were used at about the same rate and extent. During the early stages of growth B. fibrisolvens also rapidly solubilized glucuronoxylans from birchwood, larchwood, 4-O-methylglucuronoxylan, and the xylose homopolymer xylan isolated from beechwood (BEWX). In contrast to the findings for the arabinoxylans, little acid-alcohol-soluble carbohydrate remained in these cultures after 9 h of growth, except for BEWX. Initially, with birchwood, larchwood, and 4-O-methylglucuronoxylan the uronic acid components were preferentially used over the xylose. Final xylan utilization measured at 72 h for all xylans varied from 57% for CCX-A to 92% for BEWX and was correlated with the initial 12-h utilization rate for a given xylan. Since CCX-A and BEWX are both highly water insoluble, this aspect did not appear to influence overall utilization.(ABSTRACT TRUNCATED AT 250 WORDS)